The Importance of Community Legal Awareness in Land Registration - Bima, Muhammad Rinaldy (Golden Ratio of Law and Social Policy Review, 2023)
This study aims to determine and analyze the level of legal awareness of the community in Manuju District, Gowa Regency in registering their land, to find out the factors that influence the community in Manuju District, Gowa Regency in registering their land. This research uses empirical method. The research location is in Manuju District, Gowa Regency. The results of this study indicate that the level of public legal awareness in the context of land registration in Manuju District, Gowa Regency can be said to be sufficient. Judged from several aspects, namely sufficient in legal knowledge, legal understanding, legal attitudes, and community behavior. The inhibiting factors for the community in Manuju District, Gowa Regency in registering their land are lack of understanding of the functions and uses of land certificates, thinking that the land registration process takes a long time, the costs incurred in the land management process and tax payments, the supporting factors for the community in registering their land are that it can create a sense of security, obtain legal protection, can be used as strong evidence in the eyes of the law, increase selling value, and improve the community's economy, and facilitate the transfer of rights. The government should more often conduct socialization about the importance of registering land, the community should ask the local government or use the services of land officials if they do not know the land registration process.